Experimental Study on the Bending Behavior of Steel-Wood Composite Beams - Shaowei Duan; Wenzhao Zhou; Xinglong Liu; Jian Yuan; Zhifeng Wang (Advances in Civil Engineering)
This paper proposes a steel-wood composite beam with H-shaped steel beam webs glued to the wood. As a new type of composite beam, it combines the advantages of low energy consumption of wood, high permeability, and less pollution and the advantages of light weight and high strength of steel, high degree of assembly, short construction period, and less construction waste generated. Carrying out research is of great significance to improve the mechanical properties of steel-wood composite beams and promote the development of steel-wood composite structures. In this paper, three hot-rolled H-beam-larch composite beams and one pure steel beam were tested for bending capacity. The composite beams are divided into two different combinations of A and B types. The two sides of the web are connected with larch wood by structural glue to form a composite beam. The type B composite beam is a larch wood glued on both sides of the H-shaped steel web and penetrates the bolts at the same time. Through the three-point monotonic static grading loading of the composite beam, the deflection change, failure phenomenon, and form of the specimen during the experiment were observed. Under the circumstances, the ultimate bearing capacity of the test piece was changed to study the combined effect of larch and hot-rolled H-shaped steel. The results show that the overall performance of the H-shaped steel-larch composite beam is good. Bonding wooden boards on both sides of the steel beam web can improve the bearing capacity, and the form of the member is more reasonable and effective; increasing the cross-sectional size of the H-beam in the steel-wood composite beam can further improve the bearing capacity of the composite beam; adding bolt anchorage on the basis of the structural glue used in the composite beam can further improve the bearing capacity of the composite beam. The superposition principle is used to simplify the calculation of the ultimate bearing capacity of H-shaped steel-larch composite beams. Comparing the calculation results with the test results, the data are in good agreement, which can provide a design reference for the practical application of such composite beams.